Ether-linked lipids of Dermabacter hominis, a human skin actinobacterium. (March 2016) - Valero-Guillén, Pedro L.; Fernández-Natal, Isabel; Marrodán-Ciordia, Teresa; Tauch, Andreas; Soriano, Francisco
Highlights: Dermabacter hominis, a human skin actinobacterium, contains ether-linked lipids. The major phospholipid of Dermabacter hominis is plasmanyl-phosphatidyl glycerol. The major glycolipd of Dermabacter hominis is galactoyl-glucosyl-alkyl-acyl glycerol. Dermabacer hominis is able to modulate its ether-linked lipids in the presence of daptomycin. Abstract: Dermabacter hominis is a medically important actinobacterial inhabitant of human skin, although it is rarely implicated in infections. The lipid composition of D. hominis is revisited in this study in the context of its natural resistance to daptomycin, an antibiotic whose activity is influenced by membrane lipids. Thin layer chromatography and mass spectrometry revealed that this species contains phospholipids and glycolipids. Using electrospray ionization time of flight mass spectrometry (exact mass) and gas chromatography–mass spectrometry, the major phospholipid of D. hominis was identified as plasmanyl-phosphatidylglycerol (pPG), because it presented one alkyl chain and one acyl chain in the glycerol moiety of the molecule. The structure of the major glycolipid (GL1) was studied by combined gas–liquid chromatography, mass spectrometry and nuclear magnetic resonance, and was established as galactosyl-α-(1 → 2)-glucosyl-alkyl-acyl-glycerol. Lipid analyses showed differences between one daptomycin-resistant (DAP-R) strain and one daptomycin-sensitive (DAP-S) strain growing in the presence of the antibiotic: DAP-R tended to accumulate GL1 and to reduce pPG, whereas DAP-S maintained high proportions of pPG. The results demonstrate the existence of ether-linked lipids in D. hominis and reveal a differential distribution of phospholipids and glycolipids according to the sensitivity or resistance to daptomycin, although the mechanism(s) operating in the resistance to the antibiotic remain(s) to be elucidated.